A representação sociais da AIDS junto à comunidade subsídios para o atendimento psicossocial do paciente HIV - Figueiredo, Marco A.C.; Marcos, Mirlene (Brazilian Journal of Sexually Transmitted Diseases, 1997)
ln order to identify some relevant data for the elaboration of a program of AIDS information and prevention, content analysis was performed in interviews with 15 community leaders and agents in the city of Ribeirão Preto, São Paulo, Brazil. Considering the various content subcategories emphasized, 39 locutions were isolated and associated with probability (b) and evaluation (e) scales to determine the beliefs and representations about three aspects of AIDS: 1) disease, with 14 items related to contagion, psychological effect, origins, necessary reason and prevention, identifying teleologic representations associated with punishment, imprudence, human error, failure of customs and mainly family deterioration; 2) patient, with 13 items associated with profile and social interaction directed at the reinstatement of civil rights; 3) treatment, with 12 items related to lack of resources, professional/patient interaction and psychosocial approaches, identifying the scarcity of technical information with emphasis on informal care relations. Differential studies as a function of sex, age and educational levei identified more favorable propensities in younger subjects with respect to the contents related to patient (t = 2.2 7; p = .02), as well more positive attitudes with respect to treatment on the part of persons of lower educational levei (t = 2.51; p= .OI). These representations show a generality that brings the leaders close to their peers in the community in general, supporting the indication of extending programs of training and guidance also to commrrnity agents (FAPESP).